CASE STUDY: PSYCHOPRENEUR'S INTENTIONS IN PSYCHOLOGY STUDENTS IN YOGYAKARTA AND JAKARTA - Nia Wardhani; Reny Yuniasanti; Ratri Pratiwi; Wahyu Kuncoro; Muhammad Iqbal (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
The character of an entrepreneur is reflected as an individual who is able to take risks and opportunities actively, creatively, innovatively, empowered, creative, initiative, leadership abilities, and initiative in new ways of acting. Entrepreneurship in the field of educational psychology is called psychoprenuer. The low level of student intention to entrepreneurship, especially in the field of psychology development, so the purpose of this study was to determine the level and factors of psychoprenuer intentions in psychology students in Yogyakarta and Jakarta. The research method was qualitative with a two-stage case study approach, namely analyzing the psychoprenuer intention scale and the factors that influence psychoprenuer intentions in psychology students in Yogyakarta and Jakarta. Development of the psychoprenuer interview intention instrument as a form of instrument data multiplication. Then testing the psychoprenuer intention level with the previously developed psychoprenuer intention scale. The data collection method in this study used a purposive sampling method with the sample criteria of students in the psychology department. Higher education can be a factor that influences the increase in the intention of psychology students to become psychopreneurs. To encourage students' intentions to become psychopreneurs, it is necessary to formulate a curriculum with related fields, this needs to be reviewed so that psychology graduates are able to adapt to the digital era and become a solution during the COVID-19 pandemic. Several factors that influence entrepreneurial intentions such as environment, family, education, personal values, age and gender. Environment, family and education are external factors while personal values, age and gender are internal factors that influence individual intentions to become entrepreneurs.